Outcome of late preterm newborns in Upper Egypt - Alkassem Algameel; Manal Elhawary; Sayed Amin; Marwa Abd Elmenem (SpringerOpen, 2020)
Abstract Background The incidence of preterm births is increasing and has become a global health concern. This study aimed to compare the outcome of late preterm (LPT) to full term (FT) neonates at two large hospitals in Upper Egypt. Results Out of 250 newborns included in the study, 180 (72%) were FT and 70 (28%) were LPT. More than half of the LPT newborns (52.9%) were admitted to the neonatal intensive care unit (NICU), compared with 26.7% of FT newborns. Delivery of LPT was associated with an increased risk of neonatal morbidity, including jaundice requiring phototherapy (34.3% vs. 7.8%), respiratory morbidities (32.9% vs. 13.9%), hypoglycemia (8.6% vs. 1.7 %), and convulsions (4.3% vs. 0.6%). Conclusions LPT neonates were more susceptible to suffer from jaundice and respiratory distress among other morbidities. They also had a higher rate of NICU admission, longer duration of NICU stay, as well as a higher mortality rate. The best treatment of late prematurity is to prevent it. Public and professional awareness of the problems associated with late prematurity should be highlighted. Follow-up programs for early detection and intervention for long term complications are recommended.